Incidence trends of surgical complications after oesophagectomy for oesophageal cancer: a population-based, nationwide cohort study in Finland over 30 years - Ville E.J. Sirviö; Jari V. Räsänen; Olli Helminen; Mika Helmiö; Heikki Huhta; Raija Kallio; Vesa Koivukangas; Arto Kokkola; Simo Laine; Elina Lietzen; Sanna Meriläinen; Vesa-Matti Pohjanen; et al. (World Journal of Surgical Oncology)
Abstract Background Knowledge on the incidence of surgical complications after oesophagectomy for oesophageal cancer in nationwide practice is scarce. The aim of this study was to assess complication trends after oesophagectomy in a nationwide, population-based, unselected cohort. Methods All patients undergoing oesophagectomy for oesophageal cancer in Finland in 1987–2016 were included. All complications defined by the Esophagectomy Complications Consensus Group (ECCG) were reported in three 10-year periods. Chi-square test and Kruskal-Wallis test were used to compare outcomes in these periods. Results A total of 1493 patients were included. From 1987 to 1996 to 2007–2016, improvements were seen in the rate of major complications (49% vs. 43%, p = 0.039), length of hospital stay (19 vs. 14 days, median, p < 0.001), length of ICU-stay (3 vs. 2 days, median, p < 0.001) and 90-day mortality (17.9% vs. 5.4%, p < 0.001), while pneumonia (16% vs. 23%, p = 0.029) and anastomotic leak (8% vs. 12% in total leaks, p = 0.006 for type II leak) increased. The most common complications were pneumonia, pleural effusion requiring drainage (16% vs. 23%, p = 0.080), atrial dysrhythmia (16% vs. 15%, p = 0.464) and anastomotic leak. The most common complication categories defined by ECCG were pulmonary (36% vs. 42%, p = 0.151) and gastrointestinal (21% vs. 23%, p = 0.398) complications. Conclusions This study reports high postoperative morbidity after oesophagectomy in nationwide practice. Mortality has significantly improved during the years, and it appears that patients who would have died earlier, can now be rescued. While the relative occurrence of complications has remained constant, overall morbidity has decreased as the more severe outcomes have decreased.